(Protein Quality Analysis Of Mixed Rice-Banana “Awak” Ripe Flour Varied with African Catfish And Soybean Sprouts Flour) - Isnatur Rahmi; jumirah .; albiner siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Protein quality is an important requirement in the manufacture of complementary feeding. Standard of complementary feeding quality was >70% casein quality. This experimental research aims to analyze the protein quality of mixed rice-banana ‘Awak’ ripe flour (Musa paradisiaca var. Awak) varied with African catfish (Clarias gariepinus) and soybean sprouts flour (Glycine max L.Merrill). This research used a Completely Randomized Design with three treatments were: whey protein powder, banana ‘Awak’ ripe flour mixed african catfish and soybean sprouts flour (TPLK) and mixed of banana ‘Awak’ ripe flour and african catfish (TPL). Protein quality was calculating the value of Protein Efficiency Ratio (PER), Biological Value (BV) and Net Protein Utilization (NPU) of 18 male mices, 23 days old. This research was conducted in the Laboratory of Food Nutrition of Public Health Faculty, University of North Sumatera during October to December 2013. Further, analysis of feces and urine’s nitrogen of mice in Industry Standardization Research Center Medan (BARISTAND). Protein quality of TPLK and TPL from PER value were: 1.28 and 0.94. The results of analysis of variance (ANOVA) showed the PER value of TPLK and TPL doesn’t give a significantly different effect of the mice’s growth. The BV value were 17.33% and 14.47%, and the NPU value were 18.53% and 16.22%. Based on PER, BV and NPU values showed that TPLK and TPL hasn’t met the standard of complementary feeding appropriate 224/Menkes/SK/II/2007. It’s suggested, making TPLK and TPL flour should be done at a time so reduce the drying process repeatedly that damage the nutritional content especially protein. Besides, need further research using rats to see the difference weight gain and PER value. Keywords: Protein quality, Banana “Awak”, African Catfish, Soybean Sprouts Flour.